Biochemical and Structural Characterization of a Schiff Base in the Radical-Mediated Biosynthesis of 4-Demethylwyosine by TYW1 - Grell, Tsehai A. J. (J Am Chem Soc, 2018)
[Image: see text] TYW1 is a radical S-adenosyl-l-methionine (SAM) enzyme that catalyzes the condensation of pyruvate and N-methylguanosine to form the posttranscriptional modification, 4-demethylwyosine, in situ on transfer RNA (tRNA). Two mechanisms have been proposed for this transformation, with one of the possible mechanisms invoking a Schiff base intermediate formed between a conserved lysine residue and pyruvate. Utilizing a combination of mass spectrometry and X-ray crystallography, we have obtained evidence to support the formation of a Schiff base lysine adduct in TYW1. When (13)C labeled pyruvate is used, the mass shift of the adduct matches that of the labeled pyruvate, indicating that pyruvate is the source of the adduct. Furthermore, a crystal structure of TYW1 provides visualization of the Schiff base lysine–pyruvate adduct, which is positioned directly adjacent to the auxiliary [4Fe–4S] cluster. The adduct coordinates the unique iron of the auxiliary cluster through the lysine nitrogen and a carboxylate oxygen, reminiscent of how the radical SAM [4Fe–4S] cluster is coordinated by SAM. The structure provides insight into the binding site for tRNA and further suggests how radical SAM chemistry can be combined with Schiff base chemistry for RNA modification.